A Conceptualist Turn: The Ontological Status of Created Species in Late Greek Patristic Theology - Krausmüller, Dirk (Scrinium, 2020)
The realist ontology of Maximus the Confessor cannot be considered representative of the Greek theological discourse of his time. Several authors writing in the sixth, seventh and eighth centuries denied the existence of immanent universals in creation. This position was first formulated as a response to the nominalist Trinitarian theology of John Philoponus. As time went on, however, it began to serve a different function. It was now used to emphasise the distinction between God and creation.